Oil palm can stand the cold - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Until recently, the only oil palm variety that grew in the upland regions of Africa was the Dura type, but it has low yields of edible oil. Breeders from FAO and a Costa Rican company have now crossed it with the high-yielding Tenera type, which...